Southern Highbush Blueberry Cultivars from the University of Florida - Jeffery G. Williamson; Douglas A. Phillips; Paul Lyrene; Patricio R. Munoz (EDIS)
Southern highbush blueberries combine the fruit quality and productivity of highbush blueberries with the low chilling requirement necessary to produce a crop in the Florida climate. Written by J. G. Williamson, D. A. Phillips, P. M. Lyrene, and P. R. Munoz and published by the UF/IFAS Horticultural Sciences Department, this 13-page major revision describes current and historical southern highbush blueberry cultivars released by the University of Florida. http://edis.ifas.ufl.edu/hs1245